THE ULTRASTRUCTURE AND FUNCTION OF THE CELLS IN LYMPH FOLLOWING ANTIGENIC STIMULATION - Hall, J. G. (The Rockefeller University Press, 1967)
When a lymph node receives an antigenic stimulus the cell population in the efferent lymph changes and large basophilic cells appear. During a secondary immune response cells of this type may account for over 50% of the cells present in lymph. When examined by electron microscopy, many of these cells were found to be primitive undifferentiated blast cells with many free ribosomes in their cytoplasm and only an occasional piece of endoplasmic reticulum. Their nuclear chromatin was sparse and the nuclei contained several nucleoli. Many other cells which were judged to be more differentiated had large numbers of ribosomes arranged in clusters which took the form of rosettes or spirals. These cells also had more ergastoplasm but this occurred usually in the form of short pieces of disorganized endoplasmic reticulum. No cells with the ultrastructure of classical plasma cells were found in efferent lymph although these cells were abundant in the stimulated lymph nodes. It was shown that when the lymph which contained these cells was collected quantitatively no systemic immunity developed even though a vigorous immune response took place in the lymph node with the formation of many plasma cells. Failure of the systemic immune response to develop could not be explained merely in terms of the loss of antibody. It was concluded that these basophilic cells rather than antigen are responsible for propagating the immune response throughout the body and that they depend on an intact lymphatic pathway for their immediate transport. This view was supported by experiments which showed that these cells are capable of initiating immune responses in other lymph nodes of the same animal and of transferring active immunity between chimeric twins. The most likely explanation of these results is that the basophilic lymphoid cells carry out their messenger function by developing into plasma cells at sites remote from the site at which antigen is localized. However this has yet to be proven and the possibility remains that these mobile, highly motile, RNA-rich cells may express their messenger function by transferring information to other effector cells.